2009
DOI: 10.1063/1.3122052
|View full text |Cite
|
Sign up to set email alerts
|

Observation of surface enhanced IR absorption coefficient in alkanethiol based self-assembled monolayers on GaAs(001)

Abstract: Alkanethiol self-assembled monolayers (SAMs) of various methylene group chain lengths [HS–(CH2)n–CH3] (n=9,11,13,15,17) were fabricated on the GaAs(001) surface followed by characterization using Fourier transform infrared spectroscopy. Modal analysis of the CH2 stretching mode region (2800–3000 cm−1) showed that linear scaling of the n-dependent factors accurately reproduced the spectral data, supporting a chain-length consistent physical model upon which a measurement of the absorption coefficient was based.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 44 publications
4
27
1
Order By: Relevance
“…[17] Similarly sharp transitions were observed for lipid bilayers, [47][48][49] while more gradual frequency changes were found for LB films [25][26][27][28][29][30][31] and SAMs. [33][34][35][36][37][38][39][40][41][42][43] Within the LC temperature window, the position of the observed bands continuously decreases with decreasing temperature from 2854.7 and 2925 cm À1 at 343.0 K to 2854.1 and 2923 cm À1 at 318.1 K. The effect indicates that the degree of ordering in the LC phase is strongly temperature dependent and gradually increases with decreasing temperature. A second abrupt change of the peak positions occurs between 318.1 and 317.3 K, reflecting the transition to the solid-crystalline phase with an ideal all-trans conformation.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…[17] Similarly sharp transitions were observed for lipid bilayers, [47][48][49] while more gradual frequency changes were found for LB films [25][26][27][28][29][30][31] and SAMs. [33][34][35][36][37][38][39][40][41][42][43] Within the LC temperature window, the position of the observed bands continuously decreases with decreasing temperature from 2854.7 and 2925 cm À1 at 343.0 K to 2854.1 and 2923 cm À1 at 318.1 K. The effect indicates that the degree of ordering in the LC phase is strongly temperature dependent and gradually increases with decreasing temperature. A second abrupt change of the peak positions occurs between 318.1 and 317.3 K, reflecting the transition to the solid-crystalline phase with an ideal all-trans conformation.…”
mentioning
confidence: 88%
“…Here, the application of vibrational spectroscopy may be helpful to provide the desired information. Fourier-transform infrared (FTIR) spectroscopy has been used as a tool to monitor the local structure in organic thin-film systems including Langmuir-Blodgett (LB) films [25][26][27][28][29][30][31][32] and self-assembled monolayers (SAM) [33][34][35][36][37][38][39][40][41][42][43] . From band intensities and positions of the CH 2 antisymmetric stretching, symmetric stretching, scissoring, and rocking modes, information can be extracted on the molecular orientation, the degree of ordering, the concentration of gauche defects and even on the subcell packing (see e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] For metal surfaces such as Au, the fundamental interface applied in numerous biosensing architectures is based on the monolayer chemisorption and selfassembly of various thiol group ͑R-SH͒ molecules. [7][8][9] The formation of self-assembled monolayers ͑SAMs͒ using longchain alkanethiols on the GaAs͑001͒ surface has been studied by several authors, [10][11][12][13][14][15][16][17][18][19][20][21] and is of growing interest in the biosensing domain. This interest is in part due to the surface passivation effect demonstrated by covalent thiol bonding, 11,14,17,18,22 and in part due to the ability of the SAM to immobilize various analyte binding systems through a functional endgroup, DNA, or other biomolecular couplings including biotin.…”
Section: Introductionmentioning
confidence: 99%
“…Himmelhaus et al reported shifting of bands across the spectra, from 2813 cm -1 to 2851 cm -1 , and from 2916 cm -1 to 2919 cm -1 , indicating SAM formation [18]. Also, Marshall et al evaluated the adsorption of alkanethiols of varied chain length on GaAs (001), confirming how it is possible to determine the degree of imperfections on the SAM via analysis of the spectra between 2800 cm -1 and 3000 cm -1 [19]. Fig.…”
Section: Ftirmentioning
confidence: 96%